Analisis Penerapan Etika Bisnis Islam Pedagang Sembako Dalam Meningkatkan Loyalitas Pelanggan Di Pasar Anyar Tangerang - Sildaina Mutmainnah; Paulina Lubis; Muhammad Roihan; Rafiqi . (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2024)
This study aims to analyze the application of Islamic business ethics by grocery traders in Pasar Anyar Tangerang in increasing customer loyalty. This study uses a qualitative method with data collection techniques through observation, interviews, and documentation. The theory used in this study is the four axioms of Islamic ethics according to Syed Nawab Haider Naqvi, namely tauhid (unity), balance (equilibrium), free will, and responsibility (responsibility). The results of the study show that traders apply Islamic ethical values ​​such as honesty, religiosity, justice, good service in providing freedom of transaction to customers, and responsibility in maintaining the quality and comfort of buyers. The application of these values ​​has been proven to play a role in increasing customer loyalty, which is reflected in indicators such as repeat purchases, trust, and willingness to recommend to others. In addition, despite the challenges due to the market revitalization process, traders continue to strive to maintain the principles of Islamic ethics in trading, which has a positive impact on customer loyalty.